The positive impact of mindfulness interventions on the explicit and implicit affective attitudes toward vegetarian foods - Winkelmair, Annica; Jansen, Petra (Frontiers in Psychology, 2023)
Objectives: The main goal of our intervention study was to investigate whether two conceptually different mindfulness interventions positively impacted the explicit and implicit affective evaluations of vegetarian foods. We included possible mediating variables (e.g., wellbeing) and related our results to the stage model of self-regulated behavioral change (SSBC). Methods: We implemented a compassion and caring-based mental training (N = 31) and an adapted MBSR course (N = 34) as mindfulness interventions, and a stress-reduction course (N = 26) as the active control group. The curriculums consisted of twelve weekly group sessions á 75 minutes. All participants were tested preand post-intervention and three months after the last intervention session, answered questionnaires (mindfulness, compassion, wellbeing, items of the SSBC) and completed an explicit affective evaluation task and an affective priming task. Results: There was an improvement in the explicit attitudes toward vegetarian foods regardless of the intervention group. In the SSBC, we found a link between the explicit attitudes toward vegetarian foods and the indicated stage in the model. Multiple regression analysis revealed social and personal norms and a vegetarian/vegan diet as the only significant predictors for goal intention in the SSBC. Conclusion: The results of our study suggest that both conceptually different mindfulness interventions, as well as a stress-reduction program, have a positive impact on explicit affective attitudes toward vegetarian foods. We highlight the meaning of inner dimensions and transformation for change processes for a more sustainable diet and the role of social and personal norms.